The Characterization Of Prescribing Errors And Assessment Of The Impact Of An Educational Interventions Among Medical Officers Working In Kuala Kangsar Hospital - Ng, Chin Hui (2011)
The increasing trend of prescribing error in the healthcare institutes cause it became an issue of concern in Malaysia’s healthcare system. Pharmacist plays an important role to improve and prevent patients receiving these errors. Identification of prescribing errors is important to ensure the interventions successfully improve the prescribing errors. The seriousness of prescribing errors can be evaluated by assessing the errors’ severity. The objectives of the present study were to identify the five most common types of prescribing error characteristics, evaluate the severity of the prescribing errors incidence, determined the percentage of prescribing errors prevented by pharmacists and evaluate the effectiveness of the education intervention. A retrospective study reviewing newly written prescriptions with fulfilled criteria which wrote between 1st April and 30th May 2008 was conducted in a secondary care setting government hospital to analyse the type of prescribing errors. At the same time, the evaluation of severity of each error was done to identify the seriousness of prescribing errors in the hospital. Besides, the restrospective review of prescriptions provided the data on how far the pharmacists practicing their role in preventing prescribing errors. A prospective study on the prescriptions was conducted after 4 month period of educational interventions to evaluate the effectiveness of the improvement plan. Ninety four percent of prescribing errors were clinical potential prescribing errors.